PHYLOGEOGRAPHIC STRUCTURE OF THE COMMERCIALLY IMPOR- TANT TROPICAL TREE SPECIES, DRYOBALANOPS AROMATICA GAERTN. F. (DIPTEROCARPACEAE) REVEALED BY MICROSATELLITE MARKERS - Dwiyanti, Fifi Gus; Kamiya, Koichi; Harada, Ko (Research Center for Biology, 2014)
DWIYANTI, F.G., KAMIYA, K. & HARADA, K. 2014. Phylogeographic structure of the commercially important tropical tree species Dryobalanops aromatica Gaertn. F. (Dipterocarpaceae) revealed by microsatellite markers. Reinwardtia 14(1): 43 â 51. ? Dryobalanops aromatica Gaertn. F. (Kapur) is an economically important timber species in Southeast Asia that can serve as a good model for studying the impact of the Pleistocene glaciations on the genetic diversity and distribution of species in tropical regions. Seven polymorphic microsatellite markers were analyzed in five natural populations of D. aromatica (N = 120 individuals): Gunung Panti in Malay Peninsula, Lingga Island in Lingga Archipelago, Lambir Hills National Park, Limbang and Similajau National Park in Borneo. The level of gene diversity (HE) for the five populations was relatively high with a range from 0.571 (Similajau) to 0.729 (Gunung Panti). The high genetic diversity in the present study could be attributed to the larger refugia population sizes of D. aromatica than that of other species. The population genetic structure revealed two distinct groups: the Malay Peninsula-Lingga Archipelago and Borneo. This pattern suggests that populations in each geographical area might be the consequence of post-glacial expansion from one or two refugia, but that gene flow between different glacial refugia was fairly restricted.